2016
DOI: 10.1099/jmmcr.0.005052
|View full text |Cite
|
Sign up to set email alerts
|

Latent infection of human bocavirus accompanied by flare of chronic cough, fatigue and episodes of viral replication in an immunocompetent adult patient, Cologne, Germany

Abstract: Introduction:The human bocavirus (HBoV) is a parvovirus and is associated with mild to life-threatening acute or persisting respiratory infections, frequently accompanied by further pathogens. So far, there is limited knowledge on the mechanisms of persistence, and no reports on chronic infections or latency have been published so far.Case presentation:An immunocompetent male patient suffers from a chronic HBoV1 infection, i.e. viral DNA was detected in both serum and bronchoalveolar lavage (BAL) for >5 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…It is mainly associated with respiratory infections in all age groups (subtype 1) (reviewed by [ 5 , 6 ]), but may also display gastrointestinal symptoms (subtypes 2–4) (reviewed by [ 5 ]). After the identification of a covalently closed circular DNA [ 7 ] that most likely represents the form of a persisting genome, we and others have shown that HBoV is able to persist and induce long lasting infections in adults that result in a subclinical asymptomatic course [ 8 , 9 , 10 , 11 ] or that may go ahead with chronic symptoms like cough [ 12 ]. These data were confirmed by several findings from other groups [ 13 , 14 , 15 ] and led to the hypothesis that the virus may take a related pathophysiological route like the human hepatitis B virus by inducing fibrosis, followed by cancerogenesis in its target organs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly associated with respiratory infections in all age groups (subtype 1) (reviewed by [ 5 , 6 ]), but may also display gastrointestinal symptoms (subtypes 2–4) (reviewed by [ 5 ]). After the identification of a covalently closed circular DNA [ 7 ] that most likely represents the form of a persisting genome, we and others have shown that HBoV is able to persist and induce long lasting infections in adults that result in a subclinical asymptomatic course [ 8 , 9 , 10 , 11 ] or that may go ahead with chronic symptoms like cough [ 12 ]. These data were confirmed by several findings from other groups [ 13 , 14 , 15 ] and led to the hypothesis that the virus may take a related pathophysiological route like the human hepatitis B virus by inducing fibrosis, followed by cancerogenesis in its target organs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Encephalitis, myocarditis and hepatitis have also been reported in children infected with HBoV2-3 [2,3]. However, HBoV1 infections in adults are infrequent and documented endogenous or exogenous reinfections are rare [7][8][9][10]. In this study we report two fatal cases of adults with reactivations or reinfections of HBoV1 with respiratory tract illness and neurological deficits.…”
Section: Introductionmentioning
confidence: 61%
“…HBoV1 is not strictly a respiratory virus; it can produce viraemia and has been detected in the enteric tract, even in healthy adults [ 19 ]. The natural history of the infection has not been clearly elucidated, but it is known that HBoV1 can establish persistent infections [ 20, 21 ] and latent or episomal HBoV1 DNA has been detected in normal and pathological host tissues (tonsils, adenoids, colon) [ 18, 22–24 ]. Reinfections without clinical manifestations are also possible [ 16, 21 ].…”
Section: Introductionmentioning
confidence: 99%